Comparing clinical outcomes following 1 year of dual antiplatelet therapy in patients risk stratified by the PRECISE-DAPT and DAPT scores. (25th November 2020) - Boudreau, R; Fu, A; Barry, Q; Tran, U; Perry-Nuygen, D; Simard, T; Le May, M; Labinaz, L; Dick, A; Glover, C; Froeschl, M; Hibbert, B; et al.
Abstract: Background: Dual antiplatelet therapy (DAPT) is the standard of care following PCI. DAPT reduces ischemic events but increases bleeding risk. Duration of DAPT following PCI remains controversial. Current guidelines recommend duration be individualized based on risk of ischemia and bleeding. Although multiple strategies exist to risk stratify patients, including application of the PRECISE-DAPT and DAPT scores, there is currently no standardized risk assessment protocol. Purpose: To determine if the PRECISE-DAPT and DAPT scores can identify patients at increased risk of ischemia or bleeding in a cohort prescribed 12 months of DAPT following PCI. Methods: We calculated the PRECISE-DAPT and DAPT scores for 469 consecutive patients at baseline after PCI. Patients were grouped based on score treatment recommendation; PRECISE-DAPT prolonged or shortened (PRECISE DAPT <25 vs. ≥25) and DAPT prolonged or shortened (DAPT ≥2 vs <2). End points included 1-year rates of major adverse cardiovascular events (MACE) and TIMI major or minor bleeding. Results: Among 469 patients, mean age was 64.4 (SD 12.2); 102 (21.7%) were women. Index presentation consisted of a STEMI in 207 (44.1%), NSTEMI in 99 (21.1%), and UA in 60 (12.8%). At presentation, 174 (37.1%) were current smokers, 115 (24.5%) had a prior MI, 118 (25.2%) had diabetes, 249 (53.1%) had dyslipidemia and 281 (60.0%) were previously diagnosed as hypertensive. Overall, there was an increase in bleeding and no difference in MACE for patients with a PRECISE-DAPT score ≥25 (13.3% vs. 4.1% P<0.001). No difference in bleeding or MACE was present in patients stratified by the DAPT score. Conclusion: A PRECISE-DAPT score ≥25 was associated with an increased rate of bleeding and no difference in MACE in patients prescribed 12 months of DAPT. This supports the use of the PRECISE-DAPT as a prospective tool in clinical practice. Funding Acknowledgement: Type of funding source: None